ASPEK-ASPEK DALAM PENDIDIKAN KARAKTER - _, Maemonah (Forum Tarbiyah, 2012)
Character education as a concept to solve the problems which is currently being experienced by various educational institutions, of course, has many aspects in it. They are morality, religiosity, and psychological aspects. An examination of the aspects of character education is important since it is as part of the element in character education. By understanding these aspects, it can be understood that the existence of character must inevitably involve other aspects. Those aspects are even less complexity with character education itself. Therefore, the awareness to understand other aspects which supports as the backbone ofthe existence of character education is going to give aids in identifying, formulating and repeating the substance of character education